P174 Effect of continued treatment with pirfenidone following a ≥10% relative decline in percent predicted forced vital capacity (%FVC) in patients with idiopathic pulmonary fibrosis (IPF). (15th November 2016) - Wells, AU; Albera, C; Costabel, U; Glaspole, I; Glassberg, MK; Lancaster, L; Lederer, DJ; Pereira, CA; Swigris, JJ; Day, B-M; Chou, W; Nathan, SD
Abstract : Background: The variability in disease progression in patients with IPF complicates the assessment of treatment response. Previously a pooled analysis of three Phase 3 trials showed that patients who experienced a ≥10% absolute decline in %FVC during the first 6 months of treatment derived a clinical benefit with continued pirfenidone treatment in the subsequent 6 months [Nathan et al . ATS 2015]. To further explore the potential benefit of continued pirfenidone treatment in patients who initially experienced more modest declines, we assessed subsequent outcomes after a ≥ 10% relative decline in %FVC during the first 6 months of treatment. Methods: Source data included all patients randomised to receive pirfenidone 2403 mg/d or placebo in the ASCEND or CAPACITY trials (N = 1247). All patients with a ≥10% relative decline in%FVC were selected by the 6-month study visit. The proportion of patients in the pirfenidone and placebo groups who experienced any of the following during the subsequent 6-month interval were compared: (1) ≥10% relative decline in%FVC or death; (2) death; or (3) no further decline in %FVC. Results: Of the pooled patients that experienced an initial ≥10% relative decline in %FVC, 80 and 140 patients received pirfenidone and placebo, respectively. In the subsequent 6 months, 17 (21.3%) and 50 (35.7%) patients, respectively, experienced a ≥ 10% relative decline in %FVC or death. In addition, more patients in the pirfenidone group had no further decline in %FVC and fewer patients died compared with placebo during the subsequent 6-month interval (Table 1 ). Conclusions: In patients who experienced a ≥10% relative decline in %FVC during the first 6 months of treatment, continued treatment with pirfenidone appeared to lower the risk of %FVC decline or death during the subsequent 6 months, similar to previous results observed with a ≥10% absolute %FVC cut-off. Using relative change to calculate a ≥10% initial FVC decline identified more than twice as many patients compared to using absolute change. These findings suggest a potential benefit to continued treatment with pirfenidone despite an initial clinically meaningful decline in FVC ≥10% regardless of calculation method.